110k views
1 vote
Divide (-3x^2 - 9x) ÷ (x + 3)
please explain/show work! <33

Divide (-3x^2 - 9x) ÷ (x + 3) please explain/show work! <33-example-1
User Itsolidude
by
4.3k points

1 Answer

0 votes

Explanation:


( - 3 {x}^(2) - 9x) / (x + 3)

This is the original equation so you will open the brackets.


- 3 {x}^(2) - 9x / x + 3

The x will cross the division sign making it times x.


3 {x}^(2) - 9x * x = 3

So you will proceed to multiply the 9x by x making it;


3 {x}^(2) - 9 {x}^(2) = 3

So you will subtract 9x² from 3x² which won't be possible so it will be negative.


- 6 {x}^(2) = 3

Then you will square root both sides making it;


- \sqrt{6 {x}^(2) } = √(3)

So the ² will cancel the leaving

-6x=3

-6x=1.73(Divide both sides by -6)

x=0.288

That's the final answer.

User Beatrice Zmau
by
4.7k points